Do women’s autonomy lessen the brunt of unequal household responsibilities in the patriarchal context of semi-arid Northern Ghana? - Sulemana Ansumah Saaka; Isaac Luginaah (PLoS ONE, 2025)
Background Gendered roles and household responsibilities characterize the social fabric of many patriarchal societies where traditional norms often dictate a clear division of labor between men and women. These deeply entrenched gendered expectations, for several decades, continue to shape the daily lives, opportunities, the physical and psychological wellbeing of women. In the semi-arid regions of Ghana, patriarchy and traditional gender norms are particularly pronounced. Methods and materials Utilizing data from a cross-sectional survey (N = 1100 smallholder farmers), this study examined the role of women’s autonomy on shared-household responsibilities (SHRs). The composite measure of women’s autonomy was statistically robust (α = 0.823). Results Women’s autonomy was associated with increased odds of shared responsibility for childcare (OR=1.872; P < 0.001) but less so with laundry (OR=0.635; P < 0.001) and food preparation (OR=0.764; P < 0.05). However, female-headed households were more associated with shared responsibility for laundry (OR=5.617; P < 0.001) and food preparation (OR=2.546; P < 0.05) with no significant observation for childcare. Regarding marital structure, polygamous households were less associated with shared responsibility for laundry (OR=0.233; P < 0.01) and food preparation (OR=0.361; P < 0.01) with no significant observation for childcare. Moreover, religion, age, and household wealth significantly predicted shared household responsibilities in the study context. Conclusions Women’s autonomy is strongly associated with shared responsibility for childcare, but less associated with laundry and food preparation in Semi-Arid Northern Ghana, with notable differences based on household headship, marital structure, religion, age, and wealth. Findings underscore the need for more policies and programs that seeks to empower women at the household levels in rural agrarian settings.